2010
DOI: 10.1002/ar.21184
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Investigation of Age‐Related Changes of the Capillaries in White Matter

Abstract: We, for the first time, investigated the age-related changes of the capillaries in white matter using immunohistochemistry and stereological techniques. Ten young female (7 months) and 10 aged female (27 months) rats were used. The total length, total volume, and total surface area of the capillaries in white matter of aged rats were all significantly lower than those of young rats. The age-related changes of the capillaries in white matter may have important implications for age-related white matter atrophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…The greatest loss occurred in the corpus callosum/white matter, which, consistent with previous findings (Klein, et al, 1986), demonstrated the lowest capillary density of all regions irrespective of age. To the best of our knowledge, our report is the first to correlate age-related changes in cerebral angiogenic potential with capillary rarefaction in white matter of other than human brain, and is in strong agreement with the significant loss of white matter capillaries recently described in the aged rat (Shao, et al 2010). Both the density and gene changes noted carry particular clinical relevance as it has been suggested that age-related microvessel dropout in white matter stems from endothelial dysfunction and is causally related to leukoaraiosis (Brown and Thore, 2011) – a term referring to common neuroradiological findings on CT and MR scans (white matter “hyperintensities”) in elderly people and associated with cognitive decline, gait disturbance, urinary incontinence and depression (Zeevi, et al, 2010).…”
Section: 0 Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The greatest loss occurred in the corpus callosum/white matter, which, consistent with previous findings (Klein, et al, 1986), demonstrated the lowest capillary density of all regions irrespective of age. To the best of our knowledge, our report is the first to correlate age-related changes in cerebral angiogenic potential with capillary rarefaction in white matter of other than human brain, and is in strong agreement with the significant loss of white matter capillaries recently described in the aged rat (Shao, et al 2010). Both the density and gene changes noted carry particular clinical relevance as it has been suggested that age-related microvessel dropout in white matter stems from endothelial dysfunction and is causally related to leukoaraiosis (Brown and Thore, 2011) – a term referring to common neuroradiological findings on CT and MR scans (white matter “hyperintensities”) in elderly people and associated with cognitive decline, gait disturbance, urinary incontinence and depression (Zeevi, et al, 2010).…”
Section: 0 Discussionsupporting
confidence: 90%
“…3-D could be a factor as well. Similar to the unbiased stereological analysis of Shao et al, (2010), the confocal 3-D rendering approach used here, in which total capillary length in thick sections was determined, compensated for age-related changes in brain volume.…”
Section: 0 Discussionmentioning
confidence: 99%
“…In brain white matter, Shao et al . [87] found a decrease in capillary length (19%) and volume (24%). Klein and Michel [88] reported a 33% decline in vascular density.…”
Section: Capillary Growth and Lossmentioning
confidence: 92%
“…The young adult brain retains the ability to form vessels under hypoxic conditions, but this capacity is lost in mature and aged brains (Shao et al, 2010;Sonnotag et al, 1997;Harb et al, 2013). During early embryogenesis, vessels in the pia mater invade the brain and converge centripetally toward the ventricles.…”
Section: Changes In the Microvascular Density In The Brain During Lifementioning
confidence: 97%